CHARLES DARWIN - Green, Dan; Katstaller, Rachel; Willey, Leah (London : Laurence King Publishing Ltd, 2018)
Charles Darwin's ideas about evolution caused both outrage and wonder, and quickly made him one of the most famous men in history. From his five-year voyage across the high seas to 20 years of research, follow Darwin on his adventure to prove a theory that would change the world.
Little Guides to Great Lives is a brand new series of small-format guides introducing children to the most inspirational figures from history in a fun, accessible way
Includes index
Keywords: Darwin, Charles, -- 1809-1882 -- Juvenile literature; Naturalists -- Biography -- Juvenile literature -- Great Britain; Biography